The Republic of Kazakhstan's competitiveness of securities market - Nurgazina, A.; Gapbarov, R.A. (KazNU, 2016)
This article observes the formation, development and competitiveness of the modern Kazakhstan stock exchange market for the previous years
Keywords: "national IPO", trading volumes, development strategy, capitalization, concept of development